VARIABLE SECURITY ENVIRONMENT AS A FACTOR OF INFLUENCING THE SUSTAINABLE DEVELOPMENT OF TERRITORIAL COMMUNITIES - L.Y. Prohoniuk; A.A. Husenko (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu)
The article explores the impact of a volatile security environment on the processes of sustainable development within territorial communities. The study aims to provide a theoretical justification and practical analysis of how a volatile security environment affects the sustainable development of territorial communities. This includes identifying key threats, assessing their influence on socio-economic processes, and developing approaches to enhance community resilience in conditions of instability. A range of general scientific and specialized methods were employed in the research, including the methods of analysis and synthesis to generalize theoretical approaches to the concepts of the security environment and sustainable development; a systems approach to comprehensively examine the impact of security factors on socio-economic processes within communities; and comparative analysis to contrast the functioning of territorial communities under varying levels of security.